1414. Real-World Study of Healthcare Resource Use and Costs Associated with Inappropriate and Suboptimal Antibiotic Use Among Females with Uncomplicated Urinary Tract Infection in the United States. (4th December 2021) - Preib, Madison T; Mitrani-Gold, Fanny S; Sun, Xiaoxi; Adams, Christopher; Joshi, Ashish V
Abstract: Background: Urinary tract infections (UTIs) are the most common outpatient infection requiring medical care in the US; but, despite Infectious Diseases Society of America 2011 guidelines for treating uncomplicated UTI (uUTI), variation in prescribing practices still exists. Few studies have used real-world data (RWD) to evaluate uUTI-associated healthcare resource use (HRU) and costs. We examined HRU and direct costs associated with appropriate and optimal (AP&OP) and inappropriate or suboptimal (IA/SO) antibiotic (AB) prescribing in females with uUTI using US RWD. Methods: This retrospective cohort study used RWD from IBM MarketScan (commercial/Medicare claims) to examine uUTI-related HRU and costs (inpatient, emergency room, outpatient, pharmacy) per index uUTI episode and during 1-year follow-up among females (age ≥ 12 years) diagnosed with uUTI from July 1, 2013–December 31, 2017 (index date). Patients had an oral AB prescription ± 5 days of the index date, and continuous health plan enrollment ≥ 6 months pre/1 year post-index date; those with complicated UTI were excluded. Patients were stratified by AB prescription as follows: AP&OP = guideline-compliant and correct duration; IA/SO = guideline non-compliant/incorrect duration or re-prescription/switch within 28 days. Results: The study included 557, 669 patients. In the commercial population (n=517, 664, mean age 37.7 years), fewer patients were prescribed AP&OP (11.8%) than IA/SO (88.2%) ABs, a trend also seen in the Medicare population (n=40, 005, mean age 74.5 years). In both populations, adjusted average numbers of uUTI-related ambulatory visits and pharmacy claims were lower for the AP&OP cohort than the IA/SO cohort during index episode and 1-year followup (p < 0.0001, Table 1). In the commercial population, total adjusted uUTI-related costs were &194 (AP&OP) versus &274 (IA/SO; p < 0.0001); in the Medicare population, total adjusted uUTI-related costs were &253 (AP&OP) versus &355 (IA/SO; p < 0.0001) (Table 2). Table 1. uUTI-related HRU for commercial and Medicare populations calculated using the GLM model Table 2. uUTI-related costs for commercial and Medicare populations calculated using the GLM model Conclusion: Overall uUTI-related HRU and costs in the US were low during index episodes and follow-up. However, females with uUTI prescribed IA/SO ABs were more likely to incur higher HRU and costs than those prescribed AP&OP ABs, suggesting an unmet need for training to optimize uUTI prescribing per US guidelines. Disclosures: Madison T. Preib, MPH, STATinMED Research (Employee, Former employee of STATinMED Research, which received funding from GlaxoSmithKline plc. to conduct this study) Fanny S. Mitrani-Gold, MPH, GlaxoSmithKline plc. (Employee, Shareholder) Xiaoxi Sun, MA, STATinMED Research (Employee, Employee of STATinMED Research, which received funding from GlaxoSmithKline plc. to conduct this study) Christopher Adams, MPH, STATinMED Research (Employee, Employee of STATinMED Research, which received funding from GlaxoSmithKline plc. to conduct this study) Ashish V. Joshi, PhD, GlaxoSmithKline plc. (Employee, Shareholder)